2021
DOI: 10.1016/j.ajic.2020.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparative accuracy testing of non-contact infrared thermometers and temporal artery thermometers in an adult hospital setting

Abstract: Highlights Non-contact infrared thermometers (NCITs) are rapid, non-invasive devices. NCITs demonstrate variable accuracy levels across populations. A low sensitivity was found for temperatures over 37.5°C. NCITs accuracy depends on close adherence to operational guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 13 publications
1
49
0
7
Order By: Relevance
“…To the authors’ knowledge, this is the first IRT study which has reported face-mask type as a demographic factor and investigated its impact on measurement error. Our earlier study using NCIT devices in a hospital setting found that demographic factors (age, skin tone and gender) also impacted measurement results, so it appears that there is scope for future research to determine their precise impact on the performance of infrared measurement systems in fever-screening scenarios 12 . Finally, we do not believe that the use of masks had a significant impact on the effectiveness and efficacy of the measurements being taken.…”
Section: Discussionmentioning
confidence: 99%
“…To the authors’ knowledge, this is the first IRT study which has reported face-mask type as a demographic factor and investigated its impact on measurement error. Our earlier study using NCIT devices in a hospital setting found that demographic factors (age, skin tone and gender) also impacted measurement results, so it appears that there is scope for future research to determine their precise impact on the performance of infrared measurement systems in fever-screening scenarios 12 . Finally, we do not believe that the use of masks had a significant impact on the effectiveness and efficacy of the measurements being taken.…”
Section: Discussionmentioning
confidence: 99%
“…Most non-invasive temperature measuring modalities possess a fixed offset that is generally software-corrected [ 28 , 29 ], which was intentionally not employed over the course of this study. In many circumstances, despite values aligning closely at specific temperatures, they poorly predict the presence or absence of fever due to significant variability in the measurement [ 7 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the authors' knowledge, this is the first IRT study which has reported skin tone and face-mask type as demographic factors and investigated their impact on measurement error. Our earlier study using NCIT devices in a hospital setting found that these demographic factors (age, skin tone and gender) also impacted measurement results, so it appears that there is scope for future research to determine their precise impact on the performance of infrared measurement systems in fever-screening scenarios 12 .…”
Section: Discussionmentioning
confidence: 99%
“…These systems meet many of the criteria for a successful mass screening system, they are non-contact, require no consumables, are rapid, and in the case of IRT systems the operator can be physically distanced from the subject. While the use of NCIT devices has been explored in a hospital setting through a number of clinical trials and research articles, and that many of NCIT devices have achieved appropriate medical device approvals, these are not yet established for most IRT systems [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%